Construction of Sci-Tech Financial Ecosystem Indicators and International Comparative Research - Junfang, Zhang; Mu, Su (Frontiers in Political Science, 2022)
The development of science and technology (sci-tech) finance is conducive to improving the transformation quality of sci-tech achievements and optimizing the allocation of resources. However, the current sci-tech finance field in China is mainly promoted by the way of government work, and the theoretical research on the operation mechanism and system structure of sci-tech finance is relatively lagging. This article constructs the research framework of the sci-tech financial ecosystem from the perspective of ecology, uses the quantitative method of index design to deconstruct the gap between China and other major countries in the world, and analyzes the reasons and enlightenment. It is expected to provide decision-making support for relevant policies from the perspective of top-level design while promoting theoretical research.